GE_GERICHTE C/15355/2012 vom 10. Februar 2014 - GE Cour de justice (2014)
BAIL À LOYER; CONSIGNATION EN JUSTICE; ACTION EN CONTESTATION; LOYER INITIAL; FORMULE OFFICIELLE | CPC.317.2; CO.270.2; CO.269d; OBLF.19; CO.259g.1